Inventarisasi Tanaman Obat di Desa Bontotangnga Kecamatan Bontolempangan Kabupaten Gowa Sulawesi Selatan - T, Riska; Arifuddin, Widiastini; Liana, Alin (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Medicinal plants are an effective source of traditional medicine that has been used for generations to prevent and treat diseases. Inventory of medicinal plants needs to be done to collect and compile data on the types and potential of medicinal plants so that it can be used as guidelines in their utilization. This study aims to inventory the medicinal plants used in Bontotangnga Village, Bontolempangan District, Gowa Regency, South Sulawesi. This research is a descriptive survey study using qualitative approach. The data collection process was conducted through observation, and interviews. The technique of determining informants used purposive sampling. In the inventory process, data collection was carried out by collecting medicinal plant data including common names, scientific names, families, plant parts used, processing methods, and diseases treated. The results of the study showed that the types of medicinal plants used in Bontotangnga Village were 44 species from 22 families used to treat 35 types of diseases. Among the 22 families found, the Zingiberaceae family is the dominant medicinal plant used by the people of Bontotangnga Village to treat diseases. The most commonly used part of the plant is the leaves, which are usually prepared by boiling. Keywords: Inventory, Medicinal Plants, Bontotangnga Village